Retrospective cohort study evaluating the efficacy and safety of an orthopaedic consultant‐led virtual fracture clinic in an Australian level 1 trauma centre. Issue 7 (18th January 2021) - Cavka, Bernarda; Cross, Emily; Montvida, Olga; Plunkett, George; Oppy, Andrew; Bucknill, Andrew; Treseder, Thomas
Abstract: Background: In Australian health care, the consistent rise in demand for orthopaedic outpatient clinic services is creating marked challenges in the provision of quality care. This study investigates the efficacy and safety of a virtual fracture clinic (VFC) as an alternative model of care for the management of acute injuries and musculoskeletal conditions in the Australian public hospital setting. Methods: A retrospective cohort study of consecutive emergency department (ED) referrals to the Department of Orthopaedic Surgery was conducted comparing outcomes prior to (November 2015–February 2017) and after (March 2017–June 2018) implementation of a VFC. The primary outcome measures assessed were the proportion of referrals virtually discharged and unplanned 30‐day ED re‐attendance rates. Results: A total of 737 (36.4%) referrals managed by the VFC were discharged without requiring orthopaedic outpatient clinic attendance. The rate of unplanned ED re‐attendances was 5.2% post‐VFC implementation compared to 6.5% at baseline ( P = 0.01). VFC implementation was also associated with reductions in the average number of orthopaedic outpatient clinic attendances per referral (1.1 versus 1.7, P < 0.01) and the number of referrals lost to follow‐up (7.2% versus 14.7%, P < 0.01). In addition, patient wait times for first contact by the orthopaedic team were significantly reduced from a median of 7 (IQR 5, 9) days to 2 (IQR 1, 3) days post‐intervention ( P < 0.01). No complications or adverse events were reported. Conclusion: This study demonstrates that a VFC is applicable to the Australian healthcare system, and can lead to effective and safe provision of orthopaedic outpatient care. Abstract : This study demonstrates that a consultant‐led virtual fracture clinic model is an effective and safe intervention applicable to the Australian healthcare system, reducing in‐person outpatient clinic activity with no adverse effect on safety.